Qualitative Analysis of Cosmological Models inf(R)-Gravity - Avagyan, R. M.; Chubaryan, E. V.; Harutyunyan, G. H.; Saharian, A. A.
The spatially at cosmological models are investigated within the framework of f(R)-gravity. An equivalent representation in the form of a scalar-tensor theory is discussed. For the general case of the f(R) function, the corresponding cosmological equations are presented in the form of a third order autonomous dynamical system. The qualitative analysis of the latter is given in the absence of nongravitational matter. Various special cases of the function F(R) are considered and the corresponding phase portraits are depicted. The possibility for the realization of a phase with accelerated expansion of the Universe is discussed.
Keywords: Astronomy